Assessing the Effectiveness of Eco-friendly Dust Suppressants Used to Abate Dust Emission from Mine Haul Roads - Guo, Xingyun (Curtin University, 2018)
This thesis consists of two parts, literature review and experimental investigation. The first part is a literature review of eco-friendly dust suppressant. Firstly, this part gives an introduction of haul road dust. Secondly, the mechanisms and influencing factors of dust generation are investigated. Lastly, several representative dust suppressants and evaluation methods are presented and discussed. The second part is a laboratory-based study of xanthan gum and lignosulfonate in haul road dust control.